Late Palaeozoic lithostratigraphy of the Andean Precordillera revisited (San Juan Province, Argentina) - Colombo, F.; Limarino, C.O.; Spalletti, L.A.; Busquets, P.; Cardó, R.; Méndez-Bedia, I.; Heredia, N. (Journal of Iberian Geology, 2014)
New data on some neopalaeozoic lithostratigraphic units of the central sector of the Argentinean Precordillera are presented. The western Precordillera displays occasional outcrops of siliciclastic rocks of the Late Palaeozoic. These rocks are separated by two main unconformities related to the development of the Chanic (Upper Devonian-early Carboniferous) and Gondwanan (late Carboniferous-early Permian) orogens. A major unconformity marks the beginning of the Andean cycle in middle Permian times. The Del Ratón Formation (800 m) in the studied area is made up of conglomerates and can be divided into two units. The basal part (Lower Member) was deposited in a fjord environment. The Upper Member was generated by an alluvial system that was mainly dominated by upper flow-regime plane beds, whereas its uppermost part accumulated in a fan delta setting. The clast provenance and the main palaeocurrents suggest the existence of a significant topographic high to the W and NW of the present outcrops. The El Planchón Formation (1400 m) is mainly composed of shales and sandstones as a result of sedimentation in a deep-sea fan environment. These lutite-dominated materials graded laterally northwards into conglomerates in a glacial setting. The Del Ratón and El Planchón formations of the Lower Carboniferous correspond to the synorogenic Chanic sedimentation (Chanic foreland basin). Thereafter, the stratigraphic succession underwent deformation which led to its prolonged subaerial exposure and rubefaction. In Permian times, a marine transgression gave rise to the Del Salto Formation (600 m), which is constituted by beach deposits with some aeolian reworking and which lies unconformably over the Lower Carboniferous rocks. Conglomerates (Quebrada del Alumbre Formation, 100 m) produced by an alluvial system prograded episodically into coastal areas. The Escombrera Formation (350 m) is composed of beach deposits prograding seawards. This formation probably represents the end of the Palaeozoic sedimentary record. Thereafter, a playa-lake and an alluvial fan system were generated (Quebrada de la Arena Formation). This unit (750 m) was the last infill of the Gondwanan retroarc foreland, the total thickness of which was about 4000 m.